Chronotopes of law in William Faulkner’s novels, 1930-1939 (Altre Modernità, 2016)
The essay analyzes Faulkner’s As I Lay Dying (1930), Sanctuary (1931), Light in August (1932), and If I Forget Thee, Jerusalem (1939), focusing on the narrative and narratological interaction between the traditional chronotopes of law (the trial, the prison), the horizontal chronotopes of the barn, the ‘shuttered’ house, and the river, and the vertical chronotopes of the fire and the flood. The vertical chronotopes deployed attempt to challenge the official system of the law, using deeply embedded in Southern obsession for miscegenation (the rape and murder of a white woman and the lynching of an alleged mulatto) as catalysts.  However, it is the contention of this essay, no real change is engendered to human or legal justice. With the truth literally destroyed fire and water, the characters’ quest is perpetually thrust back into the stasis of non-contemporaneity.